Protein based biomarkers for non-invasive Covid-19 detection (2020)
COVID-19 has become a substantial lethal disease worldwide, and early diagnosis is a significant concern for this virus. Currently, RT-PCR is being used worldwide for the detection of this virus with human to human transmission. Furthermore, the recent develop biosensor leading to others diagnosis approach but being invasive are painful and time taking. Another possibility can be protein-based biomarkers as an application of biosensors for detection and early diagnostics. Considering the other approach, that is, microfluidics-based biosensor, though being a non-invasive method, will be restricting virus transmission. This review commences with the recent develop biosensor for Covid-19 detection and listing down the available biomarkers with their secretion range comparison of normal to COVID-19 patients through clinical analysis in china and concludes with the future approach for the diagnosis.